Daridorexant, a Recently Approved Dual Orexin Receptor Antagonists (DORA) in Treatment of Insomnia - Dwaipayan Sarathi Chakraborty; Shouvik Choudhury; Sandeep Lahiry (Sleep Science, 2023)
Insomnia is one of the major challenges in medical science nowadays as it leads to great socio-economic burden by impairing daytime function as well as the development of exhaustion, depression, and memory disturbance in affected individuals. Several important classes of drugs have been tried, including the BZDs and non-BZD hypnotics. Available drugs to combat this disease have the limitations of abuse potential, tolerance, and cognitive impairment. In some instances, withdrawal symptoms have been observed upon the abrupt cessation of those drugs. The Orexin system has been very recently targeted as a therapeutic option to overcome those limitations. Treatment of insomnia with Daridorexant as a Dual Orexin Receptor Antagonist (DORA) has been evaluated in several preclinical and clinical studies. Available information obtained from those studies has shown a promising future for this drug in the management of insomnia. Beyond its effectiveness in insomnia, it has been successfully used in patients suffering from obstructive sleep apnoea, chronic obstructed airway disease (COAD), Alzheimer's disease (AD), hypertension, and cardiovascular disorders. Larger studies need to address the safety issues as well as obtain robust pharmacovigilance information to safeguard the risk-benefit aspect of this drug in insomniac adults.